Challenges of diagnostics and treatment of non-specific mental health disorders in neurosyphilis - K. Matuzevičius; A. Bagdonaitė (Neurologijos seminarai)
Syphilis has been a health hazard worldwide since its existence, often causing long term disability or even death. Even though in Lithuania the incidence of syphilis has been slowly decreasing over several years, we still see many patients with different stages of the dis ease in the hospital setting. In this article, we present a unique and challenging case of a 52 year-old woman with neurosyphilis with a very polymorphic clinical presentation. We discuss the diagnostic and treatment difficulties, compare our case with the experience of other authors and provide our own findings on this topic.